2002
DOI: 10.1128/mcb.22.9.2883-2892.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of the Transcription Factor Nrf2 by Cancer Chemopreventive Agents: Role of Antioxidant Response Element-Like Sequences in the nrf2 Promoter

Abstract: Induction of phase 2 enzymes, which neutralize reactive electrophiles and act as indirect antioxidants, is an important mechanism for protection against carcinogenesis. The transcription factor Nrf2, which binds to the antioxidant response element (ARE) found in the upstream regulatory region of many phase 2 genes, is essential for the induction of these enzymes. We have investigated the effect of the potent enzyme inducer and anticarcinogen 3H-1,2-dithiole-3-thione (D3T) on the fate of Nrf2 in murine keratino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

28
357
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 552 publications
(386 citation statements)
references
References 46 publications
28
357
0
1
Order By: Relevance
“…These findings are consistent with other studies that have demonstrated that Nrf2 mRNA levels are unaffected by various inducers of ARE activity (13,39). A more recent study, however, reported that the expression of Nrf2 was increased in murine keratinocytes by 3H-1,2-dithiole-3-thione (D3T), but this effect was attributed to an increase in the rate of Nrf2 transcription (40). These results are contradictory to those observed in this densitometer, and the Nrf2 values were plotted after normalization with those of GAPDH.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are consistent with other studies that have demonstrated that Nrf2 mRNA levels are unaffected by various inducers of ARE activity (13,39). A more recent study, however, reported that the expression of Nrf2 was increased in murine keratinocytes by 3H-1,2-dithiole-3-thione (D3T), but this effect was attributed to an increase in the rate of Nrf2 transcription (40). These results are contradictory to those observed in this densitometer, and the Nrf2 values were plotted after normalization with those of GAPDH.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, stimulating protein expression of Nrf2 appears to be another possible mechanism. Some natural anti-oxidant agents have been shown to increase protein expression level of Nrf2 (Kwak et al, 2002;Nguyen et al, 2003;Stewart et al, 2003). In the present study, we have shown that treatment with EDG enhanced the level of Nrf2 in nucleus (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…The major active metabolite of I3C, diindolylmethane (DIM), induces expression of GADD45a, a DNA damage-responsive gene and putative tumour suppressor (Carter et al, 2002). Indole-3-carbinol can activate two pathways linked to cancer prevention: (1) aryl hydrocarbon receptor (AhR) signalling (which leads to expression of phase I enzymes (e.g., CYP1A1) via the xenobiotic response element) and (2) antioxidant/electrophilic response element signalling (resulting in expression of phase II detoxifying enzymes: e.g., oxido-reductases and glutathione-S-transferases) (Chen et al, 1998;Hayes and McMahon, 2001;Kwak et al, 2002). Thus, the ability of I3C to induce enzymes that metabolise genotoxic agents may contribute to cancer prevention.…”
mentioning
confidence: 99%